Usages and value of Facebook as a tool for the fight against gender violence in Mexico - Navarro, Celina; Martínez García, Luisa; Vialás Fernández, Simón (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2018)
Gender violence is a global problem but with more worrying realities in certain regions and countries. This is the case of Mexico where 7 women die every day. Given this scenario and in response to the government’s inability to resolve this constant violation of women’s human rights, in recent years different political actions have been carried out to eradicate this violence. In some cases, these are energized by governmental institutions but to a large extent these actions are carried out by organized civil society. Starting from the conception that the Internet and social networks are fundamental tools for the activism in the 21st century, as well as for feminism, this study aims, from a critical perspective, to analyze the use and appreciation of Facebook by the organizations that fight to eradicate gender violence in Mexico. Through a quantitative methodology we have obtained a descriptive map of the active pages of Facebook on this subject. With the qualitative part, conducting in-depth interviews with activist associations that use the social network, we have identified the dynamics of appropriation and use of the platform. Our results indicate that the entities use Facebook in an uncritical way but they manage to have an impact against gender violence since it becomes a platform that creates a notion of sorority and is perceived as a friendly platform where women feel safe to denounce cases of violence.
Keywords: activism; ciberfeminism; femicide; social networks; sorority.